2020
DOI: 10.3389/fmicb.2020.00769
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Two Foreign Genes by a Newcastle Disease Virus Vector From the Optimal Insertion Sites through a Combination of the ITU and IRES-Dependent Expression Approaches

Abstract: Many Newcastle disease virus (NDV) strains have been developed as vectors to express a foreign gene (FG) for vaccine and cancer therapy purposes. The non-coding region between the phosphoprotein (P) and matrix protein (M) genes and the non-coding region behind the NP gene open reading frame (ORF) in the NDV genome have been identified as the optimal insertion sites for efficient FG expression through the independent transcription unit (ITU) and the internal ribosomal entry site (IRES) dependent expression appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, this strategy ensures the expression of foreign proteins and the replication of viruses. He et al [65] also confirmed the above view by combining IRES and ITU to recombine NDV to express REF and EGFP in 2020, suggesting that the combination of two or more foreign proteins expressed in this way is a promising and feasible approach.…”
Section: Engineered Ndv As An Improved Cancer Vaccinementioning
confidence: 84%
“…Therefore, this strategy ensures the expression of foreign proteins and the replication of viruses. He et al [65] also confirmed the above view by combining IRES and ITU to recombine NDV to express REF and EGFP in 2020, suggesting that the combination of two or more foreign proteins expressed in this way is a promising and feasible approach.…”
Section: Engineered Ndv As An Improved Cancer Vaccinementioning
confidence: 84%
“…A majority of recombinant NDVs expressing one foreign gene (FG) as vaccines or biological therapies express through either an independent transcription unit (ITU) or an internal ribosomal entry site (IRES) approach [ 29 , 32 , 33 ]. The efficacy of these two strategies has been investigated, showing that the ITU approach was more efficient than that through the IRES approach [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of recombinant NDVs expressing one foreign gene (FG) as vaccines or biological therapies express through either an independent transcription unit (ITU) or an internal ribosomal entry site (IRES) approach [ 29 , 32 , 33 ]. The efficacy of these two strategies has been investigated, showing that the ITU approach was more efficient than that through the IRES approach [ 32 ]. The expression levels of FGs through ITU at different genomic locations were variable and the optimal insertion site in NDV genome for efficient expression has been identified as the non-coding region between the P and M genes [ 16 , 17 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…NDV constructs bearing genes encoding the SARS-CoV S protein [ 28 ] and the SARS-CoV-2 S protein [ 27 ], both around 3.8 kb in size, have been successfully generated, demonstrating this vector’s capacity for inserts in this size range. NDV has also been shown to tolerate multiple transgenes [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] using different co-expression strategies [ 59 ]. Each foreign gene must be flanked by untranslated regions (UTRs) of NDV genes called gene start (GS) and gene end (GE) sequences ( Figure 1 ).…”
Section: Designing and Generating Recombinant Ndvmentioning
confidence: 99%